2017
DOI: 10.1111/dom.13118
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative continuation of metformin does not improve glycaemic control in patients with type 2 diabetes: A randomized controlled trial

Abstract: Historically, metformin was withheld before surgery for fear of metformin-associated lactic acidosis. Currently, however, this risk is deemed to be low and guidelines have moved towards the continuation of metformin. We hypothesized that continuing metformin peri-operatively would lower postoperative serum glucose level without an effect on plasma lactate levels. We performed a single-blind multicentre randomized controlled trial in people with type 2 diabetes mellitus scheduled for non-cardiac surgery and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…20,21 The safety profile of metformin is further supported by a subsequent Cochrane review that found no clear association between the use of metformin and an increase in the development of lactic acidosis. 20 It was reassuring to see that no significant changes in lactate were observed by Hulst et al 9 and is consistent with previous reports. 14,15 Thus, the continuation of metformin peri-operatively appears to be both a viable and safe intervention.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…20,21 The safety profile of metformin is further supported by a subsequent Cochrane review that found no clear association between the use of metformin and an increase in the development of lactic acidosis. 20 It was reassuring to see that no significant changes in lactate were observed by Hulst et al 9 and is consistent with previous reports. 14,15 Thus, the continuation of metformin peri-operatively appears to be both a viable and safe intervention.…”
supporting
confidence: 87%
“…Taken together, the potential benefits of metformin on peri‐operative glycaemic control in patients undergoing non‐cardiac surgery should not yet be discounted. Although the trial by Hulst et al failed to detect any changes in glucose control, this was not an unexpected result given the large number of patients in the study who underwent metabolic surgery, which could have significantly confounded the results. If the metformin and control groups were not balanced in terms of the number of patients who underwent metabolic surgery, this would also have had an impact on the glycaemic outcomes.…”
Section: Conflict Of Interestmentioning
confidence: 90%
“…While continuation of metformin during this period is considered to be safe, there was little evidence of benefit in doing so, and therefore, we designed the respective randomized controlled trial. 1 As pointed out by Dr Brown and Dr Paul, a possible limitation of our study is the high proportion of cases of bariatric surgery (46%) included. They suggest that early metabolic changes, observed after bariatric surgery independently of weight loss, may have had an impact on our results.…”
mentioning
confidence: 91%
“…We thank Dr Brown and Dr Paul for their insightful commentary on our study and the subject of perioperative continuation of metformin, stressing again the importance of perioperative hyperglycaemia and treatment of diabetes mellitus (DM). The mentioned guidelines indeed suggest considering continuation of metformin in the perioperative period, despite previous concerns about metformin‐associated lactic acidosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation